Spaced perturbations of “predator-prey” dynamic systems - Baranovskii, Serhij; Bomba, Andrii (Моделювання, керування та інформаційні технології, 2019)
A mathematical model of “predator-prey” population interactions with regard to diffusive and migratory factors of individuals’ dispersal in space is considered. In case the diffusive and migratory constituents are small as compared to other constituents of the process, it is suggested to search for the solution of a singular perturbed model problem in terms of asymptotical series